Kakšne novosti prinaša Zakon o čezmejnem izvajanju storitev za podjetja in napotene delavce - Snoj, Jurij (Delavci in delodajalci, 2017)
In addition to adjusting the national regulations of this field to the EU law, the aim of Transnational Provision of Services Act (hereafter ZČmIS) is to strengthen the rule of law, ensure legal security, as well as protection of human rights and fundamental freedoms.
Keywords: direktive; Evropska unija; pravna ureditev; skupni trg; storitve; trg delovne sile; zaposleni